The Metabolic and Neurochemical Etiopathology of Passive Exposition to Alcohol Consumers - Nery Lamothe; Mara Lamothe; Daniel Lamothe; Ernesto Villanueva; Pilar Bueno; Alejandro Alonso-Altamirano; Adriana Clemente-Herrera; Estuardo Hernández; Francisco Guillermo Castillo-Vázquez; Andrės Gerardo Roche (Journal of Public Health International, 2021)
A narrative review considers metabolic and neurochemical pathways implicated in passive exposure to alcohol consumers, discussing health effects and research needs.
Keywords: Metabolic